Analisis Risiko Proyek Pengembangan Perangkat Lunak Menggunakan Kerangka Kerja ISO 31000 - Nuris, Amin Maruf; Maharani, Aditya; Rachmadita, Renanda Nia (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2021)
PT. Duta Media Cipta (DMC) is a control system and IT company based in the city of Surabaya, this company focuses on procurement, maintenance and repair services for ship equipment, both mechanical and electrical. As an information technology company, PT. DMC is committed to being a trusted IT and control system company. In working on the project, PT. DMC has not implemented risk management for every software development project it has worked on. Some of the risks that are often faced in working on software projects at PT. DMC are project risks such as technical, cost, and project scheduling which are sometimes not in accordance with the established plan and cause cost and time losses to the company. So in this study using ISO 31000 as a framework in analyzing potential risks. The application of risk assessment consists of 3 stages, namely risk identification, risk analysis, and risk evaluation. The results of this study found that there are 4 risks with 26 sub-risks, of which there are 6 sub-risks that are prioritized and require risk management.